Impacts of telecommuting on time use and travel: A case study of a neighborhood telecommuting center in Stockholm. (April 2021) - Bieser, Jan C.T.; Vaddadi, Bhavana; Kramers, Anna; Höjer, Mattias; Hilty, Lorenz M.
Highlights: Overall travel time on telecommuting days is shorter than on employer office days. Local work centers can facilitate use of energy-efficient commute transport modes. On home office days, telecommuters mainly use the car for private travel. Telecommuting can increase energy requirements for non-travel activities. Abstract: While telecommuting (TC) research heavily discusses travel impacts of home-based TC, little is known about impacts of working from a neighborhood TC center on travel and non-travel activities and their energy requirements. We conduct a case study on the impacts of the work location (employer's office, TC center, home) on time use and travel using data collected in a neighborhood TC center in Stockholm. Our results show that telecommuters more frequently replaced working from the TC center for working from the more distant employer's office than for working from home. On TC center and home office days, diarists spent less time traveling, and on home office days more time on chores and leisure than on employer office days. When working from the TC center instead of the employer's office, telecommuters frequently used the same or more energy-efficient commute modes, e.g. biking instead of the car, which was feasible because the TC center is in the local neighborhood. However, when working from home, diarists mainly used the car for private travel. Thus, energy savings of TC can be increased by providing energy-efficient transport options or local access to non-work destinations to telecommuters. TC energy impacts depend also on changes to energy requirements for non-travel activities, for space heating/cooling/lighting at all work locations, and systemic TC effects (e.g. residential relocation), which can only be observed in the long term. Thus, future TC assessments should take an even broader perspective in terms of travel and non-travel activities, their energy requirements, and systemic effects.